“White Trash” Wisdom: Proverbs 9 Deconstructed - Mark Sneed (Journal of Hebrew Scriptures, 2009)
Though Woman Wisdom has often been viewed as a positive figure for feminism, I will show that the picture is much grimmer. The article has two parts. First, I will demonstrate that the personification of wisdom reinscribes the typical ideology of the time along gender, social class, and racial lines. The eroticization of wisdom as female actually excludes the woman from the search for truth and knowledge because it assumes its adherents are male. Woman Wisdom is shown to be upper class, while Folly is poor. And Woman Wisdom is shown to be xenophobic in her preference for Jewish boys. Second, wisdom/folly, the dominant dichotomy of these chapters, will be shown to deconstruct, showing how both Woman Wisdom and Folly are inextricably connected and partake of each other’s identity. The boundary between the two begins to blur.